TEXTBOOKS IN ENGLISH LANGUAGE TEACHING IN VIEW OF GLOBALISATION, LOCALISATION AND GLOCALISATION - Toprakçı, Nihal; Ozaydınlı, Belgin (International Online Journal of Education and Teaching, 2021)
Recent research has revealed that the relationship between language and culture stands out as an important factor in language teaching. The purpose of this study was to examine the cultural content of ninth-grade textbooks used in teaching English based on the World-Readiness Standards for Learning Languages (WRSLL), and also from teachers’ opinions. The study was conducted via phenomenology, one of the qualitative research paradigms. In accordance with the aim of the study, three textbooks prepared with global, local, and glocal perspectives were selected. As data collection tools, the WRSLL form and also semi-structured interviews were conducted, and with descriptive and content analysis techniques applied in analysing the collected data. The study group consisted of 50 English teachers who had used all three of the selected textbooks. The study’s findings revealed that the book with a local perspective was found to be inadequate in terms of its cultural content. It was also concluded that, according to the participant teachers’ views, there was no need to prepare a localised book for the Turkish context, and that universal books containing less localised content would be more suited to effective teaching. From this perspective, it is suggested that the regulations on textbook preparation issued by the Turkish Ministry of National Education (MoNE) should be revised in accordance with requirements of gaining intercultural knowledge.